The American Southeast at the End of the Ice Age - Tune, Jesse W., 1983-; Smallwood, Ashley M.; Miller, D. Shane (Darcy Shane), 1982- (Book collections on Project MUSE., 2022)
"In 1996, the University of Alabama Press published a prodigious benchmark volume, The Paleoindian and Early Archaic Southeast, edited by David G. Anderson and Kenneth E. Sassaman. It was the first to provide a state-by-state record of the Paleolithic and early Archaic eras (to approximately 8,000 years ago) in this region as well as models to interpret data excavated from those eras. It summarized what was known of the peoples who lived in the Southeast when ice sheets covered the northern part of the continent and mammals such as elephants, saber-toothed tigers, and ground sloths roamed the landscape. In the United States, the Southeast has some of most robust data on these eras. The American Southeast at the End of the Ice Age is the updated, definitive synthesis of current archaeological research gleaned from an array of experts in the region. The volume is organized in three parts: state records, the regional perspective, and perspective and future directions. State-by-state chapter overviews of the eras are followed by chapters with regional coverage on lithics (point types), submerged archaeology, gatherers, megafauna, chipped-stone technology, and spatial demography. Chapters on ethical concerns regarding the use of data from avocational collections, insight from outside the Southeast, and considerations for future research round out the volume. The contributors address five questions: When did people first arrive? How did they get there? Who were they? How did they adapt to local resources and environmental change? Then what?"--